Introduction to open quantum systems - Erciyas, Abdurrahman. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
The purpose of this study is to introduce open quantum systems to the reader. The study should not be taken as a comprehensive resource on the subject. In the study, some of the fundamental concepts of quantum mechanics have been given with a di erent point of view; thus, it is intended to take the reader beyond the orthodox attitude of standard quantum mechanics. Here, we will start with the introduction of basic tools to understand the open quantum systems. In the study, system-plusreservoir model, which is the most fundamental model to understand the nature of open systems, will be introduced. Then, quantum evolutions will be generalized and how non-unitary evolution will be de ned will be shown. In this study, only markovian open systems will be introduced. Finally, the example of quantum harmonic oscillator, which is isomorphic to most quantum systems, will be given as a physical example for explaining the dynamics of open systems.
Keywords: Quantum systems.; Quantum theory.